Verallgemeinerung des Wiman-Valironschen Satzes für ganze Funktionen mehrer komplexen Veränderlichen - Streliz, S. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ш. Стрелиц. Обобщение теоремы Вимана-Валирона для функции многих комплексных переменныхŠ. Strelicas. Vimano-Valirono teoremos apibendrinimas daugelio kintamųjų sveikosioms funkcijoms